Clinical presentation, diagnosis, and treatment of atrioesophageal fistula resulting from atrial fibrillation ablation. (27th July 2021) - Della Rocca, Domenico G.; Magnocavallo, Michele; Natale, Veronica N.; Gianni, Carola; Mohanty, Sanghamitra; Trivedi, Chintan; Lavalle, Carlo; Forleo, Giovanni B.; Tarantino, Nicola; Romero, Jorge; Zhang, Xiadong; Bassiouny, Mohamed; et al.
Abstract: Background: Atrioesophageal fistula (AEF) is a worrisome complication of atrial fibrillation (AF) ablation. Its clinical manifestations and time course are unpredictable and may contribute to diagnostic and treatment delays. We conducted a systematic review of all available cases of AEF, aiming at characterizing clinical presentation, time course, diagnostic pitfalls, and outcomes. Methods: The digital search retrieved 150 studies containing 257 cases, 238 (92.6%) of which with a confirmed diagnosis of AEF and 19 (7.4%) of pericardioesophageal fistula. Results: The median time from ablation to symptom onset was 21 days (interquartile range [IQR]: 11–28). Neurological abnormalities were documented in 75% of patients. Compared to patients seen by a specialist, those evaluated at a walk‐in clinic or community hospital had a significantly greater delay between symptom onset and hospital admission (median: 2.5 day [IQR: 1–8] vs. 1 day [IQR: 1–5); p = .03). Overall, 198 patients underwent a chest scan (computed tomography [CT]: 192 patients and magnetic resonance imaging [MRI]: 6 patients), 48 (24.2%; 46 CT and 2 MRI) of whom had normal/unremarkable findings. Time from hospital admission to diagnostic confirmation was significantly longer in patients with a first normal/unremarkable chest scan ( p < .001). Overall mortality rate was 59.3% and 26.0% survivors had residual neurological deficits at the time of discharge. Conclusions: Since healthcare professionals of any specialty might be involved in treating AEF patients, awareness of the clinical manifestations, diagnostic pitfalls, and time course, as well as an early contact with the treating electrophysiologist for a coordinated interdisciplinary medical effort, are pivotal to prevent diagnostic delays and reduce mortality.